NUEVOS DASYPODIDAE (MAMMALIA, XENARTHRA) DEL MIOCENO TARDÍO DEL VALLE DEL CAJÓN, CATAMARCA, ARGENTINA (Ameghiniana, 2014)
In this paper the folIowing Dasypodidae are reponed from Valle del Cajón: Neophractus martae n. gen. n. sp., Vetelia gandhii n. sp., Chasicotatus peiranoi n. sp., Vassalia maxima and Paleuphractus sp. The fossiliferous beds extend into the northern area of valle del Cajón (26°33'/ 26°36' S; 66°17'/ 66°23' W). The materials here reported come from the Subsequences I1b and Ilc of Playa del Zorro aloformation. The age of these levels is regarded as Huayquerian, and they are correlated with the Andalhualá Forrnation in valle de Santa María (Catamarca, Argentina).